Lateral Access Minimally Invasive Spine Surgery - Wang, Michael Y.; Sama, Andrew A.; Uribe, Juan S. (Springer International Publishing : Imprint: Springer, 2017)
This well-illustrated textbook is the first comprehensive and authoritative source of information on minimally invasive lateral access spine surgery. It covers all aspects of the subject, including patient selection, approach and monitoring techniques, soft tissue management, application in a variety of pathologies, technical nuances, and the prevention and management of complications. In addition, current controversies in the field are discussed and the biomechanics of lateral spinal reconstruction, the physiologic benefits, and cost implications are explained. Over the past decade, the emergence of minimally invasive lateral access spine surgery has created a revolution in spine treatment. This trend began with the introduction of extreme lateral interbody fusion, a totally new spinal procedure. In recent years, the conversion of more than 15% of lumbar spinal fusion procedures to a lateral approach has been due to the unique advantages of this approach over conventional anterior or posterior surgery. All major purveyors of spinal products and implants have entered this market enthusiastically, and all major spinal societies now conduct annual cadaveric and didactic courses to teach the technique. As use of the lateral approach in spinal surgery has become more popular, so its diversity and complexity have increased. Nevertheless, coverage in the literature is typically limited to single chapters, and the spinal surgeon seeking to achieve optimal results must rely on chance discussions with colleagues at meetings to learn the latest information. Lateral Access Minimally Invasive Spine Surgery is designed to fill this vacuum. Written by world experts on the topic, it will be an excellent resource for both beginning and experienced surgeons.